Energy calculation of 2s2 1S, 2p2 1D, 3s2 1S, 3p2 1D, 3d2 1G, 4p2 1D, 4d2 1D, 4f2 1I doubly excited states using a new wave function to four terms for 2≤Z≤15. (June 2016) - Sow, B.; Sow, M.; Gning, Y.; Traore, A.; Ndao, A.S.; Wague, A.
Abstract: Calculation of the energy levels of atoms and ions with 2 ≤ Z ≤ 15 are carried out in this paper using a Hyllerass approximation. The method used is one of Screen Constant by Nuclear Charge Unit to calculate the total energy of two-electron atomic systems in ground and different doubly excited states. Employing a new wave function including correlation, we were able to calculate excited states (nl) 2 ( n ≤ 4 ). The Comparison of these results with the ones of other methods shows a good agreement. Highlights: Accurate energy for doubly excited states of He-like systems 2 ≤ Z ≤ 15 . Well-comparable results to theoretical literature values. Satisfactory agreements with theoretical calculations.